The Influence of Exile - Rankin, Sara K. (2016)
Belonging is a fundamental human need, but human instincts are Janus-faced and equally strong is the drive to exclude. This exclusive impulse, which this Article calls the influence of exile, reaches beyond interpersonal dynamics when empowered groups use laws and policies to restrict marginalized groups' access to public space. Jim Crow, Anti-Okie, and Sundown Town laws are among many notorious examples. But the influence of exile perseveres today: it has found a new incarnation in the stigmatization and spatial regulation of visible poverty, as laws that criminalize and eject visibly poor people from public space proliferate across the nation. These laws reify popular attitudes toward visible poverty, harming not only the visibly poor but also society as a whole. This Article seeks to expose and explain how the influence of exile operates; in doing so, it argues against the use of the criminal justice system as a response to visible poverty. In its place, this Article argues for more effective and efficient responses that take as their starting point an individual right to exist in public space, which for many visibly poor people is tantamount to a right to exist at all